A mixture model with application to discrete competing risks data - Ndlovu, Bonginkosi D.; Melesse, Sileshi F.; Zewotir, Temesgen; Zewotir, Temesgen (South African Statistical Journal, 2019)
In this paper, we modify the continuous time mixture competing risks model (Larson and Dinse, 1985) to handle discrete competing risks data. The main result of the model is an alternate regression expression for the cumulative incidence function. The structure of the regression expression for the cumulative incidence function under this model, and the proportional hazards assumption for the conditional hazard rates with piece-wise constant baseline conditional hazards, combine to allow for another means to assess the covariate effects on the cumulative incidence function. This benefit comes at some computational costs because the parameters are estimated via an EM algorithm. The proposed model is applied to real data and it is found that it improves the exercise of evaluating the covariate effects on the cumulative incidence function compared to other discrete competing risks models.